Textbook of Aramaic Ostraca from Idumea, Volume 1: Dossiers 1-10 ; 401 Commodity Chits - Porten, Bezalel; Yardeni, Ada; Kletzing, Matt; Han, Eugen (Eisenbrauns, 2014)
Intro -- COVER Front -- Copyright Page -- Table of Contents -- Introduction.